NG2 Proteoglycan Promotes Endothelial Cell Motility and Angiogenesis via Engagement of Galectin-3 and α3β1 Integrin - Fukushi, Jun-ichi (The American Society for Cell Biology, 2004)
The NG2 proteoglycan is expressed by microvascular pericytes in newly formed blood vessels. We have used in vitro and in vivo models to investigate the role of NG2 in cross-talk between pericytes and endothelial cells (EC). Binding of soluble NG2 to the EC surface induces cell motility and multicellular network formation in vitro and stimulates corneal angiogenesis in vivo. Biochemical data demonstrate the involvement of both galectin-3 and α3β1 integrin in the EC response to NG2 and show that NG2, galectin-3, and α3β1 form a complex on the cell surface. Transmembrane signaling via α3β1 is responsible for EC motility and morphogenesis in this system. Galectin-3–dependent oligomerization may potentiate NG2-mediated activation of α3β1. In conjunction with recent studies demonstrating the early involvement of pericytes in angiogenesis, these data suggest that pericyte-derived NG2 is an important factor in promoting EC migration and morphogenesis during the early stages of neovascularization.